Decreased frontal, striatal and cerebellar activation in adults with ADHD during an adaptive delay discounting task - WHELAN, ROBERT; GARAVAN, HUGH; O'CONNELL, REDMOND (My University, 2015)
An important characteristic of childhood attention-deficit/hyperactivity disorder (ADHD) is a bias towards small immediate versus larger delayed rewards, but it is not known if this symptom is also a feature of adult ADHD. A delay-discounting task was administered to participants with adult ADHD and a comparison group in conjunction with functional magnetic resonance imaging. Participants responded to a series of questions that required judgments between small sums of money available immediately and larger sums obtained after a temporal delay. Question parameters were adjusted by an adaptive algorithm designed to converge on each participant's discounting indifference point, an individual set point at which there is equal valuation of both choices. In all participants, robust task activation was observed in regions previously identified in functional imaging studies of delay discounting. However, adults with ADHD showed less task activation in a number of regions including the dorsolateral prefrontal cortex, superior frontal gyrus, anterior cingulate, caudate nucleus and declive of the cerebellum. Additionally, the degree to which a participant discounted delayed rewards was inversely related to task activation in the cerebellum. The results suggest that the bias towards immediate rewards in childhood ADHD may not persist behaviorally, but instead present in adulthood as alterations in frontostriatal and frontocerebellar networks.
PUBLISHED
Keywords: ADHD